2020
DOI: 10.1016/j.matt.2020.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Robust and High-Performance Electrodes via Crumpled Au-CNT Forests for Stretchable Supercapacitors

Abstract: A robust and high-performance stretchable electrode was developed via crumpled Au-coated carbon nanotube (Au-CNT) forest transferred onto a compliant substrate. Compared with a pure CNT forest electrode, the Au-CNT forest electrode exhibits one order magnitude lower resistance. The stretchable Au-CNT forest electrodes and supercapacitors demonstrate significant improvement in mechanical reliability and electrochemical stability under extremely large strains. This research offers a facile approach to fabricate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…[ 19,20 ] However, numerous applications (e.g., stretchable interconnects, wearable displays, capacitive tactile sensors, printed circuit boards, deformable supercapacitors) demand stretchable conductors that maintain their electrical conductivity upon deformation and thus require a very low gauge factor, ideally zero. [ 21–28 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 19,20 ] However, numerous applications (e.g., stretchable interconnects, wearable displays, capacitive tactile sensors, printed circuit boards, deformable supercapacitors) demand stretchable conductors that maintain their electrical conductivity upon deformation and thus require a very low gauge factor, ideally zero. [ 21–28 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, they charge and discharge rapidly with massive bursts of energy while discharging. Generally, carbon nanomaterials such as CNTs and graphene have been explored for use in supercapacitors due to their low cost, high surface area, and long cycle lifetime [ 159 ]. Chen et al demonstrated that highly stretchable supercapacitors with high electrochemical performance can easily be fabricated using a method involving the wrapping of CNT thin film synthesized by chemical vapor deposition around pre-stretched elastic wires, and twisting two of these CNT-wrapped elastic wires precoated with poly(vinyl alcohol) powder (PVA)/H 3 PO 4 /water hydrogel as the electrolyte ( Figure 13 a(i)) [ 160 ].…”
Section: Power Sourcesmentioning
confidence: 99%
“…Supercapacitors based on CNT-wrapped wire showed excellent capacitance up to 30.7 F g −1 and high stretchability of up to a strain of 350%. Cao and Zhou’s team demonstrated a facile approach of fabricating crumpled CNT forest-based supercapacitors on a pre-strained elastomer substrate ( Figure 13 c) [ 159 ]. Such a crumpled CNT forest has the advantages of easy access due to its pore structure, short ion transport time, and low ionic diffusion resistance.…”
Section: Power Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…An efficient control over the results of carbon synthesis may be provided by noble metal nanoparticles (NPs) serving as catalysers. As an example, the recent publication [ 2 ] demonstrated a convenient approach for fabrication of highly stretchable supercapacitors based on vertically aligned nanotubes and nanowires with embedded gold NPs that allowed achieving an exceptional and robust electrochemical performance. The graphene sheets with incorporated metal NPs [ 3 ] are highly promising for THz-generation because of the possibility to inject hot carriers from the NPs to the graphene matrix.…”
Section: Introductionmentioning
confidence: 99%